Implikatur Pidato Prabowo Subianto pada Acara "Penutupan Kongres III Partai Nasdem" - Wiwit Regina Afni; Achmad Wahidy; Masnunah Masnunah (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study aims to analyze the use of implications and patterns of violations and compliance with the principle of Grice's cooperation in Prabowo Subianto's political speech. This study uses a qualitative descriptive method with data in the form of transcripts from the YouTube video "Closing of the Third Congress of the Nasdem Party" on August 25, 2024. Data collection was carried out using the free listening technique and the recording technique. The results of the study showed that in the political speech analyzed there were 39 implicit speeches, consisting of 16 conventional implicit speeches (41%) and 23 unconventional implicit speeches (59%). In addition, it was also found that S 37 maximum violations and 13 maximum compliance. The most dominant violations were the maximum quantity (43%), followed by the maximum quality (16%), the maximum relevance (22%), and the maximum method (19%). Meanwhile, compliance with the maxim occurred most in the maxim of quality (31%), followed by maxim of relevance (23%) and maxim of means (15%). These findings suggest that politicians often use communication strategies by providing exaggerated information, conveying implicit messages, or shifting the topic of conversation to shape an image and influence public opinion.